A ginseng PgTIP1 gene whose protein biological activity related to Ser128 residue confers faster growth and enhanced salt stress tolerance in Arabidopsis. (May 2015) - Li, Jia; Cai, Weiming
Highlights: PgTIP1 is a functional water channel protein but the mutation of Ser 128 abolished water channel. Overexpression of PgTIP1 enhances plant growth but S128A or S128D does not enhance plant growth. PgTIP1 confers salt stress tolerance to Arabidopsis but mutation of Ser 128 in PgTIP1 abolishes this phenotype. PgTIP1 alters the expression of stress-related genes in transgenic Arabidopsis . Abstract: Water movement across cellular membranes is mostly regulated by aquaporins. A tonoplast intrinsic protein PgTIP1 from Panax ginseng has been found to play an important role in plant growth and development, and also in the response of plants to abiotic stress. However, the regulation of its function and activity remains unknown. To answer this question, mutated forms of PgTIP1 were made by replacing Ser 128 with Ala (named S128A) or Asp (named S128D), and also by replacing Thr 54 with Ala (named T54A) or Asp (named T54D). Then, wild type or mutated PgTIP1 was expressed in yeast and water transport was monitored in protoplasts. The substitution of Ser 128 abolished the water channel activity of PgTIP1, while the substitution of Thr 54 did not inhibit its activity. Moreover, the overexpression of PgTIP1 but not S128A or S128D in Arabidopsis significantly increased plant growth as determined by biomass production, it also had a beneficial effect on salt stress tolerance. Importantly, the overexpression of PgTIP1 led to the altered expression of stress-related genes, which made the plants more tolerant to salt stress. Our results demonstrated that PgTIP1 conferred faster growth and enhanced tolerance to salt in Arabidopsis, and that its biological activity related to Ser 128 residue.